IDENTITAS GERAKAN MUHAMMADIYAH - Hikmah, Nur; Nurfadillah, Andi; Lama Bawa, Dahlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Muhammadiyah is one of the largest Islamic organizations in Indonesia, founded as a reformist movement (tajdid) based on the Qur’an and Sunnah. Since its establishment by KH. Ahmad Dahlan in 1912, Muhammadiyah has demonstrated a distinctive identity as a modern, rational, and progressive Islamic movement. This article aims to comprehensively examine the identity of the Muhammadiyah movement, including its basic concepts, formative values and principles, as well as its challenges and relevance in the modern era. The method employed is a literature study using a descriptive-analytical approach to various Kemuhammadiyahan-related sources. The findings indicate that Muhammadiyah’s identity is constructed upon the principles of purification of Islamic teachings, reform (tajdid), rationality, moderation, independence, and social concern manifested through charitable enterprises. Amid the challenges of globalization, digitalization, and contemporary religious dynamics, the concept of Progressive Islam (Islam Berkemajuan) promoted by Muhammadiyah remains relevant and contributes significantly to building a religious, progressive, and civilized society.